POLITENESS STRATEGIES IN DIGITAL CODE-SWITCHING, A PRAGMATIC ANALYSIS - Rustamova Mohinabonu Sherzod qizi, (TADQIQOTLAR, 2026)
Abstract: This study investigates how politeness strategies are realized through digital code-switching in bilingual and multilingual online interactions. By analyzing 500 social media posts, instant messaging conversations, and forum discussions, the study identifies patterns in language alternation that reflect social relationships, respect, and identity  management. The findings reveal that speakers strategically use code-switching  to  express  positive  politeness  (solidarity  and  appreciation),  negative politeness (respect and mitigation of  imposition), and off-record strategies (indirect communication).  Additionally,  digital  features  such  as  emojis,  hashtags,  and abbreviations significantly influence the use and interpretation of code-switching. The study  highlights  the pragmatic  importance  of digital  code-switching  and its  role in maintaining  effective,  polite,  and  socially  aware  communication  in  online environments.